Agora é samba! Saberes afro-passistagógicos de mulheres gaúchas - Pires, Karen Tolentino de (2022)
The present study was carried out during the years 2018 to 2022 with Passistas from Rio Grande do Sul, seeking to understand how their Pedagogies occur, which are called, in this research, Passistagogies. To carry out this study, a research method was created aimed at a study with Black Women, which is based on four stages: knowing, listening, seeing and learning. Only after these steps it is possible to acquire a true academic knowledge about Black Women. It was investigated that Black Women become Passistas mainly through their family and other Black Women in the samba sociability environment. It was found that there is a correlation between being a dancer and being a Queen or Godmother of Carnaval, as well as of the samba school drums. It was noticed an empowerment acquired through samba, and on the other hand, a neglect in love relationships because they are passistas. It was considered that each Passista has its Passistagogy, which is in accordance with their experiences and identities. However, It was noticed that often Passistagogy occurs unintentionally, because just the fact of being samba in a School Samba, in many cases, is enough to encorage other Black Women to become Passistas. It was understood that the Samba School isvthe besta environment for learning samba, especially due to the presence of drumming which has an intimate relationship with dance, a striking feature of afro-brazilian manifestations. It was found that even with an increasing number of choreographies in recent years, creativity and improvisation continue to be one of the main points of Passistas. Ultimately, It was observed that in addition to being a short career, there is a devaluation of work, which cannot be sustained with its performance. So, most of dancers from Rio Grande do Sul, dance for love with little or no financial return.